Gendered Obstacles in Educational Leadership Among Female Leaders - Gaihre, Bishnu Subedi (An ENDEAVOUR: Journal of Academia and Research, 2026)
Female leadership in education today has become the subject of attention due to its potentiality to promote inclusive decision-making system, diversity, and innovation. Despite such benefits, females remain underrepresented in leading positions in educational institutions, particularly in the communities reigned by strong patriarchal norms and values such as Nepal. This paper explored the gendered obstacles that hinder women’s progression into educational leadership roles and examined how women leaders handled and overcame such challenges. Adopting an interpretivist paradigm, the researcher followed a qualitative narrative inquiry approach collecting data using unstructured interviews to three female head teachers of public secondary schools in Syangja district, Nepal. The findings revealed that women head teachers encountered multiple barriers, including societal skepticism regarding women’s authority, gender stereotypes establishing women as soft or emotional, institutional biases in the schools in leadership selection, and challenges in balancing family responsibilities and profession. Despite such challenges, the women head teachers applied several strategies, such as developing plans and policies, involving in continuous professional development, building collaborative leadership, focusing on transparent decision-making procedures, maintaining committee-based management, and creating strong engagement with stakeholders such as teachers, students, parents, and the outer community. The findings remark the need of female leadership for better institutional reforms, gender-inclusive policies, and collaborative leadership atmosphere to ensure equitable opportunities for females in educational leadership in Nepal.